2008
DOI: 10.3748/wjg.14.3292
|View full text |Cite
|
Sign up to set email alerts
|

Historical reflections on autoimmune hepatitis

Abstract: Autoimmune hepatitis (AIH), initially known as chronic active or active chronic hepatitis (and by various other names), first came under clinical notice in the late 1940s. However, quite likely, chronic active hepatitis (CAH) had been observed prior to this and was attributed to a persistently destructive virus infection of the liver. An earlier (and controversial) designation in 1956 as lupoid hepatitis was derived from associated L.E. cell test positivity and emphasized accompanying multisystem features and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 64 publications
0
27
0
4
Order By: Relevance
“…Hastalığın patofizyolojisi tam olarak bilinmemekle birlikte, tetikleyici risk faktörleri sonucunda oluşan otoimmünitenin hepatoselüler inflamasyona neden olduğu düşünülmektedir. 4 Otoimmüniteyi tetikleyen bu risk faktörleri ise, kızamık, kızamık-çık, akut hepatit A, akut hepatit B, Ebstein-Barr virüs gibi viral enfeksiyonlar, insan lökosit antijen sınıf 1 B8 veya sınıf 2 DR3 ve DR52A gibi genetik predispozan faktörler, metildopa, diklofenak, minosiklin, nitrofurantoin, atorvastatin gibi farmakolojik etmenlerdir. 5 Otoimmün hepatit tanısı zor konulan bir hastalıktır.…”
Section: Discussionunclassified
“…Hastalığın patofizyolojisi tam olarak bilinmemekle birlikte, tetikleyici risk faktörleri sonucunda oluşan otoimmünitenin hepatoselüler inflamasyona neden olduğu düşünülmektedir. 4 Otoimmüniteyi tetikleyen bu risk faktörleri ise, kızamık, kızamık-çık, akut hepatit A, akut hepatit B, Ebstein-Barr virüs gibi viral enfeksiyonlar, insan lökosit antijen sınıf 1 B8 veya sınıf 2 DR3 ve DR52A gibi genetik predispozan faktörler, metildopa, diklofenak, minosiklin, nitrofurantoin, atorvastatin gibi farmakolojik etmenlerdir. 5 Otoimmün hepatit tanısı zor konulan bir hastalıktır.…”
Section: Discussionunclassified
“…80% of autoimmune hepatitis is type 1, 4% is type 2 and 3% is type 3 which is a rare type (2,3,5,8). The type in which autoantibodies can not be identified, but clinical and histological examination are compatible with AIH is called undefined AIH (11).…”
Section: Discussionmentioning
confidence: 99%
“…It is characterised by the presence of various autoantibodies in the serum, high level of gammaglobulin and mononuclear cell infiltration in the periportal or portal area histopathologically (motheaten necrosis) (1)(2)(3)(4)(5). According to immunoserologic findings four types of AIH were defined as type 1, type 2, type 3 and undefined autoimmune hepatitis (6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…AIH has a complex genetic transmission pattern that is not clearly established. One or more genes increase or decrease the possibility of genetic transmission alone or in combination (1,2,5). In several studies, some alleles were found to display differences in amino acid sequences (6)(7)(8), and an increased frequency of human leukocyte antigen (HLA) A1, B8 and DR3/DR4 has been reported in patients with type 1 AIH [9].…”
mentioning
confidence: 99%
“…Presently, three types of AIH are distinguished: type 1 AIH is characterized by antinuclear antibodies (ANA) and/or smooth muscle antibodies (SMA) in the serum in association with hypergammaglobulinemia; type 2 AIH patients have anti-LKM 1 (type 1 liver/kidney microsome) antibodies in serum, and the majority of the cases are children; and type 3 AIH is characterized by the presence of antibodies against soluble liver antigen/liver-pancreas antigen (SLA/LP) (1,3). Some patients share the clinical and histological features of AIH without the presence of immunological markers (autoantibodies) required for sub-classification.…”
mentioning
confidence: 99%